PENGARUH PEMBERIAN TACTILE STIMULATION TERHADAP PENURUNAN GANGGUAN SENSORIK DAN PERILAKU PADA ANAK DI YAYASAN PENDIDIKAN AUTIS MUTIARA HATI SURABAYA - Abdullah, Khabib; Ichlasul Amalia Romadhona; Atik Swandari (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Background: Children with developmental disabilities often experience sensory and behavioral disorders that impact social, emotional, and academic abilities. Physiotherapy plays a crucial role in providing Tactile Stimulation, a structured tactile stimulation that stimulates the sensory and motor nervous systems, to support sensory integration, emotional regulation, and improved adaptive behavior. This study aimed to determine the effect of Tactile Stimulation on reducing sensory and behavioral disorders in children at Autism Education Foundation of Mutiara Hati, Surabaya Branch. Research Methods: This study was a field experiment with a one-group pretest-posttest design. A sample of 12 children was selected based on inclusion and exclusion criteria from a pool of 38 children with sensory and behavioral disorders. The intervention, in the form of Tactile Stimulation, was administered in six sessions over two weeks, each lasting 30 minutes. Measurements were conducted using the Short Sensory Profile (SSP) questionnaire for sensory aspects, and teacher interviews were conducted to evaluate behavioral changes. Normality was tested using the Shapiro-Wilk test, and hypothesis testing used the Wilcoxon test with a significance level of p<0.05. Results: The statistical test results showed no statistically significant effect between the pretest and posttest (p>0.05). However, clinically, 8 of the 12 children showed a decrease in SSP scores (66.7%), and teacher interviews indicated positive changes in behavior, such as increased calmness, focus, and ability to follow instructions. Conclusion: Tactile Stimulation did not have a statistically significant effect, but showed a positive clinical impact on the majority of children.